Astronomical Shoptalk in Paris, ca 1246: An Edition and Translation of John of London’s Letter to R. de Guedingue - Nothaft, C. Philipp E. (Aestimatio, 2021)
A unique source on the practical aspects of the scientia astrorum (astronomy and astrology) in medieval Europe has come down to us in the shape of a letter written shortly after 1246 by John of London, an astronomer based in Paris. John used the letter to answer eight questions on technical problems posed to him by his addressee, a certain R. de Guedingue, with subject matters ranging from the rate of precession to the dates of the so-called Dog Days. The article makes this source available via a critical edition (based upon three manuscripts) and an accompanying English translation. An introduction discusses the background and transmission of John’s letter as well as the identities of the letter writer and addressee. The edition and translation are followed by commentaries elucidating the background to each of the eight questions and John’s answers to them.